Photoaffinity labeling of rat androgen binding protein. - Taylor, C A (1980)
The photoinactivation and photoaffinity labeling of androgen binding sites present in cytosol prepared from intact sexually mature rat epididymides have been demonstrated by using unlabeled and [3H]-labeled 17 beta-hydroxy-4,6-androstadien-3-one. Both photoinactivation and photolabeling are dependent upon exposure to light. These processes are inhibited when photolysis is conducted in the presence of the photoinert compound 17 beta-hydroxy-5 alpha-androstan-3-one, suggesting that steroid-specific sites are involved in the reactions. The labeled steroid-specific product of photolysis is macromolecular with a molecular weight of 47,000 as determined by electrophoresis on polyacrylamide gels containing NaDodSO4, and proteinaceous because digestion of the cytosol with pronase before photolysis eliminates steroid-specific binding. After photolysis, the protein-steroid complex has the ability to withstand dissociation during electrophoresis under denaturing conditions, and unlabeled 17 beta-hydroxy-5 alpha-androstan-3-one fails to displace the label from the complex. Thus, the binding of [3H]17 beta-hydroxy-4,6-androstadien-3-one to the cytosolic protein is covalent. This steroid-specific product is identified as an androgen binding protein of testicular origin by its comigration with native androgen binding protein on nondenaturing polyacrylamide gels and by its molecular weight which is within the range reported for androgen binding protein subunits.